Desain Kemasan Produk UMKM Dizayu Menggunakan Model Kano - Perwasih, Mayang; Triha, Hadigufri; Putri, Ranti Mustika (SURYA TEKNIKA, 2026)
Dizayu is a local micro, small, and medium enterprise in Maninjau, West Sumatra, producing smoked fish known as salai bada as a regional souvenir product. The existing packaging is relatively simple, lacks adequate product information, and has not fully performed its protective, promotional, and branding functions. This study aims to identify packaging attributes based on consumer preferences and propose a new packaging design using the Kano Model. A descriptive quantitative approach was applied by distributing questionnaires to 50 respondents. The data were analyzed using the Kano evaluation table to classify 20 packaging attributes, followed by the calculation of Better and Worse coefficients to determine design priorities. The results indicate that composition information, logo, expiration date, recyclability, portability, affordability, oil resistance, ergonomic grip, durability, product image, and lightweight packaging are classified as one-dimensional attributes. Tear resistance and bright colors are categorized as must-be attributes, while the ziplock feature is classified as attractive. Plain design, transparency, single-use packaging, variety, simplicity, and luxury impression are categorized as indifferent. The proposed packaging design is a 18 cm x 25 cm pouch made from OPP, PET, and aluminum foil, featuring bright colors, complete product information, product imagery, a recycling symbol, and a ziplock feature as a differentiating element.